2014
DOI: 10.4085/1062-6050-49.1.04
|View full text |Cite
|
Sign up to set email alerts
|

Disinhibitory Interventions and Voluntary Quadriceps Activation: A Systematic Review

Abstract: Objective: To determine the effects of various therapeutic interventions on increasing voluntary quadriceps muscle activation.Background: Decreased voluntary quadriceps activation is commonly associated with knee injury. Recently, research has focused on developing specific disinhibitory interventions to improve voluntary quadriceps activation; yet, it remains unknown which interventions are most effective in promoting this improvement.Data Sources: We searched Web of Science from January 1, 1965 through Septe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 46 publications
(118 reference statements)
0
48
0
3
Order By: Relevance
“…Researchers investigating the immediate and short-term effects of disinhibitory modalities alone or coupled with strengthening exercises have reported similar phenomena of improved knee-extension strength 18 and facilitation of voluntary activation, 18,19 indicating that this approach to treatment may improve muscle function through reduced inhibitory signaling 41 rather than the peripheral muscle hypertrophy associated with longer-duration strength-training interventions. Further investigation into the effects of a prolonged strengthening intervention, including disinhibitory modalities on quadriceps function or broader measures of lower extremity function, is an essential next step to improve the clinical applicability of our findings.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Researchers investigating the immediate and short-term effects of disinhibitory modalities alone or coupled with strengthening exercises have reported similar phenomena of improved knee-extension strength 18 and facilitation of voluntary activation, 18,19 indicating that this approach to treatment may improve muscle function through reduced inhibitory signaling 41 rather than the peripheral muscle hypertrophy associated with longer-duration strength-training interventions. Further investigation into the effects of a prolonged strengthening intervention, including disinhibitory modalities on quadriceps function or broader measures of lower extremity function, is an essential next step to improve the clinical applicability of our findings.…”
Section: Discussionmentioning
confidence: 97%
“…Addressing the underlying source of inhibition using a disinhibitory modality may provide a short treatment window (30À90 minutes 21À24 ) during a rehabilitation session throughout which the effect of rehabilitation-based strengthening exercises on quadriceps function may be maximized. 18,25 This strategy has been shown to induce clinically meaningful improvements in knee-extension strength, 19,26 quadriceps activation, 19,26 and lower extremity biomechanics 17 over 2-to 4-week interventions; however, the effect of this intervention style on limb symmetry in quadriceps function among individuals with a history of ACLR has not been established. Researchers have clearly shown a positive contralateral effect, known as a crossover effect, of involved or uninvolved limb strength or functional status among healthy individuals, 16 as well as those with a history of knee-joint injury.…”
Section: ])mentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Disinhibitory modalities have recently been suggested as a clinical tool for clinicians to use to counteract the negative effects of AMI and enhance the effectiveness of therapeutic exercise. [2][3][4] Some of these modalities were originally intended for other purposes but are now hypothesized to provide disinhibitory effects, as well. For example, neuromuscular electrical stimulation (NMES) is a well-known strengthening modality that has recently been identified as having the potential to serve as a disinhibitory modality.…”
Section: Clinical Scenariomentioning
confidence: 99%
“…Therefore, disinhibitory interventions need to be selected based on the status of the patient and origin of quadriceps activation failure. A newly published systematic review by Harkey et al 15 assessed all of the disinhibitory interventions that have been reported in the literature for improving quadriceps activation. More research efforts such as these are needed to determine the best methods for treating both the spinal and supraspinal origins of quadriceps activation failure.…”
Section: Clinical Recommendationmentioning
confidence: 99%